Determination of the Immune Potential of Palatine Tonsil Cells Against Antigens of Respiratory Viruses and Microbes Based on In Vitro Studies - Melnykov, O.F.; Zabolotnyi, D.I.; Spivak, M.Y.; Timchenko, M.D.; Sambur, M.B.; Kryvokhatska, L.D.; Tupitska, O.D.; Bredun, O.Y.; Мельников, О.Ф.; Заболотний, Д.І.; Співак, М.Я.; Тимченко, М.Д.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
In recent decades, much attention has been paid to new approaches to vaccination against viruses of the respiratory group, among which the concept of local etiologically appropriate vaccination deserves attention, according to which vaccination should be carried out in the same way as infection occurs, that is, for viruses and microbes of the respiratory group – through the upper respiratory tract or orally, where the immune system of mucosal membrane and its important components – the structures of the lymphoepithelial ring -– play a significant role. The aim of the study was to determine the level of the production of antibodies to respiratory viruses and antigens of Streptococcus pyogenes and Klebsiella pneumoniae  and interferones by  palatine tonsil cells and blood mononuclear cells of patients with chronic tonsillitis. Methods. The study was conducted on palatine tonsil (PT) cell cultures obtained from 20 patients with chronic tonsillitis who underwent tonsillectomy for indications. The immunological activity of the tonsil cells in vitro was compared with that of mononuclear cells isolated from heparinized blood using a Ficoll-Verografin density gradient (d=1.077). The antibody content in the culture fluid after 24-hour cultivation of cells was determined by the levels of IgG antibodies to the SARS-CoV-2 virus antigens (using the ELISA system "Diaproph," Ukraine), anti-hemagglutinins against influenza A and B –  via the hemagglutination inhibition reaction against vaccine hemagglutinins (GCFLU, quadrivalent, GC pharma). Antibodies to human orthopneumovirus antigens were determined using the ELISA system (Euroimmun), to the Virus Epstein-Barr (EBV) capsid antigen using the Vitrotest system (Ukraine), and to Streptococcus pyogenes – using the "Granum" tests (Ukraine), to Klebsiella pneumoniae proteoglycans – via the passive hemagglutination reaction using sorption of Klebsiella antigen (Biostim, France). The content of interferons α and γ was determined using ELISA kits (Elabscience, USA). Results. The obtained data indicate more pronounced reactive manifestations of antibody formation against viral and microbial antigens of respiratory pathogens after culturing PT cells of patients with chronic tonsillitis. The highest content of antibodies in the culture fluid was determined to antigens of Influenza A and B viruses, as well as to Human orthopneumovirus antigens, and to a lesser extent – to antigens of  SARS-CoV-2 and EBV viruses. PT cells in vitro actively produced antibodies to streptolysin-O of S. pyogenes group A and weakly – to proteoglycans of K. pneumoniae. The content of α-interferon was higher in blood cells supernatants than that of γ-interferon in PT cells supernatants. Conclusions. The conducted studies indicate a high immunological potential of the palatine tonsils, even with their chronic inflammation relative to a wide range of antigens of respiratory viruses and microbes, which confirms the new concept of local vaccination through the upper respiratory tract, rather than parenterally.